ECO-FEMIN(ISM) AND HINDU(ISM): Positioning Contemporary Eco-Ethic Conversation - Naidu, Maheshvari (Journal of Dharma, 2008)
The article examines the complex cluster of issues that accrete around attempts to refract a contemporary ‘Hindu’ eco-ethic from ancient scriptural sources. So often, scholars and religious adherents alike refer back to the ‘golden eco-age’ alluded to in the various Vedic, Upanisadic and Puranic injunctions with their invocations adoring both the earth and the life it sustains. As an academic field of study within the social sciences, however, "Religion and Ecology" is a relatively recent subdiscipline of "Religion Studies."